A type of vitamin B 12 Preparation methods and applications of carbon nanotube composites co-supported with zero-valent iron nanotubes.
Patent Information
- Application Number
- CN202311663466.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-06
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-12-06
AI Technical Summary
因此,针对VB12在原位修复中易流失,稳定性差,同时为提升零价铁反应性
[0020]1)本发明合成的维生素B12和纳米零价铁共负载碳纳米管复合材料,该材料可用于原位去除和降解地下水以及土壤中的重金属类、农药类、偶氮染料类、卤代有机物类和/或硝基代有机物类污染物且具有较高的去除和降解效率;
Smart Images

Figure CN117925247B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of material preparation and environmental remediation technology, and particularly relates to a vitamin B complex. 12 Preparation method and application of carbon nanotube composite materials co-supported with nano-zero valent iron. Background Technology
[0002] Vitamin B 12 (VB 12 As a transition metal coenzyme, cobalt is the only vitamin containing a metal element. It can be naturally produced by anaerobic bacteria and is mainly synthesized by the pharmaceutical industry. It contains a cobalt ring, with the cobalt atom serving as a redox-active metal center, enabling its biocompatibility. Among all stable vitamin B12... 12 In this morphology, the central cobalt ion exhibits a +3 oxidation state; however, VB 12 Its unique function stems from free radicals, including Co. 2+ (VB 12 r) and "hypernucleophilic reagent" Co 1+ (VB 12 The properties of reduced cobalt species, including s), with various reducing agents (e.g., titanium(III) citrate, NaBH4, 1-thioglycerol ester, and acetyl gold). Therefore, VB 12 It can act as a coenzyme to catalyze a range of biological processes, including isomerization, methyl transfer, and dehalogenation. In environmental applications, reduced VB... 12 The reductive dechlorination of short-chain chlorinated hydrocarbons such as chloromethane and vinyl chloride in liquids can be facilitated by promoting electron transfer to the target organic compound. However, VB 12 Its susceptibility to loss limits its application. Immobilized cobalt amines for the dehalogenation of chlorinated pollutants can lay the foundation for the development of efficient and economical in-situ detoxification systems for halogenated pollutants.
[0003] Currently, VB 12 Commonly used electron donors in this system include titanium citrate (III) (TC), dithiothreitol (DTT), cysteine, zero-valent metals, bimetallic materials, metallic minerals, and semiconductor materials. Among these, homogeneous reducing agents such as TC are prone to loss, making recovery and reuse difficult. In practical applications, continuous addition is required, reducing the system's electron utilization rate. Furthermore, TC requires artificial preparation, which is not conducive to practical applications. Compared to homogeneous reducing agents, solid heterogeneous reducing agents have advantages such as strong practicality, easy recovery, low cost, high efficiency, and reusability. Simultaneously, the adsorption, reduction, and catalytic effects of solid-phase reducing agents on pollutants can also be compared with those of VB. 12 They work together to accelerate the reduction and dehalogenation process.
[0004] Zero-valent iron (Fe₂O₃) has strong reducing properties (E°). 0 / Fe 2+With a voltage of -0.447V and low raw material costs and abundant sources, zero-valent iron (ZV) is widely used in environmental remediation for the removal and degradation of inorganic or organic pollutants in groundwater and soil. Over the past half-century, the discovery of nano-ZV and its application in environmental remediation have greatly increased the application scope and potential of ZV. However, before large-scale production and practical application, nano-ZV still has some limitations, such as easy aggregation leading to poor actual degradation effects and failing to leverage its high activity. Furthermore, industrial production is costly and requires stringent storage conditions. Additionally, for some recalcitrant halogenated organic compounds such as ethane chloride, ZV is limited by its reducing properties and shows almost no degradation effect.
[0005] Nanotubes (CNTs) hold great potential in many fields due to their unique mechanical properties, thermal stability, and chemical stability. Therefore, targeting VB... 12 It is prone to loss and has poor stability during in-situ remediation, and it is necessary to improve the reactivity of zero-valent iron. 12 Zero-valent iron and carbon nanotubes are efficiently combined to solve the above problems. Summary of the Invention
[0006] This invention combines existing vitamin B 12 Modification techniques were used to synthesize a vitamin B complex. 12 A composite material co-loaded with zero-valent iron nanotubes was developed. This method not only boasts abundant raw material sources and simple operation, but also low cost, and yields vitamin B12. 12 The carbon nanotube co-supported composite material with zero-valent iron exhibits high removal efficiency for pollutants such as heavy metals, pesticides, azo dyes, halogenated organic compounds, and nitro-substituted organic compounds, and can be mass-produced to meet environmental remediation needs. This is achieved through the following technical solutions:
[0007] A type of vitamin B 12 A method for preparing a composite material of carbon nanotubes co-supported with zero-valent iron nanotubes includes the following steps:
[0008] 1) Take the prescribed amount of ferrous sulfate heptahydrate and carbon nanotubes, add deionized water and stir. Purge with N2 to remove dissolved oxygen to obtain a suspension emulsion.
[0009] 2) Add sodium borohydride solution dropwise to the suspension emulsion in step 1), and carry out the reduction reaction by vigorous stirring under N2 conditions. After the reduction is completed, filter the black suspension emulsion and wash it three times with ethanol / water to remove impurities, and obtain the nano-zero-valent iron-carbon nanotube composite material.
[0010] 3) Add vitamin B to the N,N-dimethylformamide solution. 12The nano-zero-valent iron-carbon nanotube composite material obtained in step 2) was ultrasonically treated, stirred at room temperature, centrifuged and the supernatant was discarded. The precipitate was washed with DMF and centrifuged twice until the supernatant was colorless. Finally, it was washed with deionized water and centrifuged twice, and then freeze-dried to obtain vitamin B1. 12 Carbon nanotube composite material co-loaded with nano-zero valent iron.
[0011] Further, in step 1), the mass ratio of nano-zero-valent iron to carbon nanotubes is 1.5-2.5:1, and the material-to-liquid ratio of carbon nanotubes to deionized water is 0.6-0.7 g: 155-165 mL. Further, in step 1), N2 is purified N2 with a purity greater than 99%.
[0012] Furthermore, the vigorous stirring time in step 2) is 30 minutes.
[0013] Further, in step 3), the ratio of the nano-zero-valent iron-carbon nanotube composite material to the N,N-dimethylformamide solution is 1g:700-800ml, and the vitamin B... 12 The mass percentage of carbon nanotubes is 0.01-0.25.
[0014] Furthermore, in step 3), the ultrasonic treatment time is 1 hour, and the stirring time at room temperature is 20 hours.
[0015] Vitamin B1 prepared by the above method 12 Application of carbon nanotube composite materials co-loaded with nano-zero valent iron in the treatment of wastewater, polluted soil and polluted groundwater.
[0016] Furthermore, the wastewater, contaminated soil, and contaminated groundwater contain at least one of heavy metals, pesticides, azo dyes, halogenated organic compounds, and / or nitro-substituted organic compounds.
[0017] Furthermore, the heavy metals include, but are not limited to, hexavalent chromium (Cr(VI)), cadmium (Cd), nickel (Ni), mercury (Hg), manganese (Mn), arsenic (As), antimony (Sb), and lead (Pb); the pesticides include, but are not limited to, atrazine, dichlorophenoxyacetic acid, polychlorinated biphenyls, and DDT; the azo dyes include, but are not limited to, Sudan Red, Orange G, and Golden Orange II; the halogenated organic compounds include, but are not limited to, carbon tetrachloride, tetrachloroethane, chloroform, tetrachloroethylene, trichloroethylene, dichloroethane, and perfluorooctane sulfonyl compounds; and the nitro-substituted organic compounds include, but are not limited to, nitrobenzene.
[0018] The innovation of this invention lies in: by using vitamin B 12 When vitamin B is co-loaded with nano-zero valent iron on carbon nanotubes, vitamin B... 12 With zero-valent iron evenly distributed on the carbon nanotubes, vitamin B in this material 12As an electron shuttle for degrading and removing pollutants, zero-valent iron provides the electrons needed to reduce and degrade pollutants; more importantly, carbon nanotubes can efficiently transfer the electrons provided by zero-valent iron, thereby completing the degradation of recalcitrant halogenated organic compounds such as ethane chloride. This composite material can ultimately transform pollutants into low- or non-polluting products, making it highly suitable for in-situ remediation of groundwater and soil.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1) Vitamin B synthesized in this invention 12 A composite material of carbon nanotubes co-loaded with nano-zero valent iron can be used for in-situ removal and degradation of heavy metals, pesticides, azo dyes, halogenated organic compounds and / or nitro-substituted organic compounds in groundwater and soil with high removal and degradation efficiency.
[0021] 2) The preparation method of this invention is simple, and vitamin B... 12 In-situ remediation can promote microbial metabolism and pollutant degradation, which is an environmentally friendly process.
[0022] 3) Vitamin B prepared by the method of this invention 12 The composite material of carbon nanotubes co-loaded with nano-zero valent iron exhibits high activity in degrading and removing pollutants, and degrades pollutants rapidly.
[0023] 4) Since most pollutants in domestic contaminated sites are dichloroethane, this technology has overcome the technical bottleneck that non-biological in-situ treatment technologies cannot degrade dichloroethane. Compared with biodegradation technology, it has the advantages of shorter remediation cycle and lower maintenance cost. Attached Figure Description
[0024] Figure 1 Vitamin B obtained in Example 1 12 TEM-EDS images of carbon nanotube composites co-loaded with nano-zero valent iron; where a is the TEM image and b is the EDS image.
[0025] Figure 2 Vitamin B obtained in Example 1 12 The effect of carbon nanotubes co-supported with nano-zero valent iron on the removal of chloroethane;
[0026] Figure 3 Vitamin B obtained in Example 2 12 Carbon nanotube composites co-loaded with zero-valent iron in different VB 12 Comparison of ethane chloride removal efficiency under different loading levels;
[0027] Figure 4 Vitamin B obtained in Example 3 12Comparison of the removal efficiency of carbon nanotubes co-supported with nano-zero valent iron for ethane chloride removal at different pH values. Detailed Implementation
[0028] The present invention will be further described below with reference to the accompanying drawings and specific embodiments in order to better understand the technical solution.
[0029] Example 1
[0030] Vitamin B 12 The preparation steps of the carbon nanotube co-supported composite material with nano-zero valent iron are as follows:
[0031] (1) In a three-necked flask, 0.66 g of carbon nanotubes and 1.0922 g of ferrous sulfate heptahydrate were mixed with 161 mL of deionized water. The mixture was then stirred in the flask and purged with purified N2 (>99%) for 1 hour to remove dissolved oxygen. Subsequently, 59 mL of a solution of 0.2982 g of sodium borohydride was added dropwise to the suspension, and the mixture was stirred vigorously under N2 conditions for half an hour. After reduction, the black suspension was filtered and washed three times with ethanol / water to remove impurities.
[0032] (2) Add 0.88g of nano-zero-valent iron-carbon nanotube composite material and 0.099g of vitamin B to 660ml of N,N-dimethylformamide solution. 12 The solution was sonicated for 1 hour and stirred at room temperature for 20 hours. Subsequently, the solution was centrifuged, and the supernatant was discarded. The precipitate was washed with DMF and centrifuged twice until the supernatant was colorless. Finally, it was washed with deionized water and centrifuged twice, then freeze-dried to obtain vitamin B12. 12 Carbon nanotube composite material co-loaded with nano-zero valent iron.
[0033] The vitamin B prepared in this embodiment 12 TEM-EDS image of carbon nanotube composite material co-supported with nano-zero valent iron is shown below Figure 1 As shown; where a is the TEM image and b is the EDS image, from Figure 1 Vitamin B can be seen in it 12 Nano-zero valent iron is evenly distributed on the surface of carbon nanotubes.
[0034] Using dichloroethane as the target pollutant, the activity of the above solution was tested. 26 mL of deoxygenated deionized water and 0.104 g of vitamin B were added to a 52 mL reagent bottle. 12 The carbon nanotube composite material was co-loaded with nano-zero valent iron, and the bottle was sealed with an aluminum cap with a PTFE septum. Then, dichloroethane stock solution was added to ensure that the initial concentration of dichloroethane was 10 ppm. The reagent bottle was then placed in a service incubator and kept at a constant temperature of 25°C.
[0035] After 7 hours of reaction, the concentration of dichloroethane was measured to be 0 ppm, indicating a degradation rate of 100%. Figure 2 As shown.
[0036] Example 2
[0037] This embodiment refers to Example 1, and uses different concentrations of vitamin B. 12 The results of the experiment on the pollutant dichloroethane are shown in Table 1.
[0038] (1) In a three-necked flask, 0.66 g of carbon nanotubes and 1.0922 g of ferrous sulfate heptahydrate were mixed with 161 mL of deionized water. The mixture was then stirred in the flask and purged with purified N2 (>99%) for 1 hour to remove dissolved oxygen. Subsequently, 59 mL of a solution of 0.2982 g of sodium borohydride was added dropwise to the suspension, and the mixture was stirred vigorously under N2 conditions for half an hour. After reduction, the black suspension was filtered and washed three times with ethanol / water to remove impurities.
[0039] (2) Add 0.88g of nano-zero-valent iron-carbon nanotube composite material and vitamin B at different mass ratios to 660ml of N,N-dimethylformamide solution. 12 (0.01-0.25) and sonicated for 1 hour, then stirred at room temperature for 20 hours. The solution was then centrifuged, and the supernatant was discarded. The precipitate was washed with DMF and centrifuged twice until the supernatant was colorless. Finally, it was washed with deionized water and centrifuged twice, then freeze-dried to obtain vitamin B. 12 A composite material of carbon nanotubes co-supported with nano-zero valent iron. Vitamin B2 prepared in this example... 12 The composite material of carbon nanotubes co-supported with nano-zero valent iron was analyzed by ICP-MS. 12 The actual load is shown in Table 2.
[0040] Using dichloroethane as the target pollutant, the activity of the above solution was tested. 26 mL of deoxygenated deionized water and 0.104 g of vitamin B were added to a 52 mL reagent bottle. 12 Carbon nanotube composites were co-loaded with nano-zero-valent iron, sealed tightly with an aluminum cap fitted with a PTFE septum, and then dichloroethane stock solution was added to ensure an initial concentration of 10 ppm. The reagent bottle was then placed in a service incubator and maintained at a constant temperature of 25°C. The results are as follows: Figure 3 As shown, degradation efficiency and VB 12 The concentration is directly proportional to the concentration.
[0041] Table 1 Vitamin B 12 The removal rate of dichloroethane by carbon nanotubes co-supported with nano-zero valent iron within 7 hours
[0042]
[0043]
[0044] Table 2
[0045]
[0046] Example 3
[0047] This embodiment refers to the experiment in Example 1, and tests were conducted on the pollutant dichloroethane at different pH values. Other technical parameters and results are shown in Table 3.
[0048] Vitamin B 12 The preparation steps of the carbon nanotube co-supported composite material with nano-zero valent iron are as follows:
[0049] (1) In a three-necked flask, 0.66 g of carbon nanotubes and 1.0922 g of ferrous sulfate heptahydrate were mixed with 161 mL of deionized water. The mixture was then stirred in the flask and purged with purified N2 (>99%) for 1 hour to remove dissolved oxygen. Subsequently, 59 mL of a solution of 0.2982 g of sodium borohydride was added dropwise to the suspension, and the mixture was stirred vigorously under N2 conditions for half an hour. After reduction, the black suspension was filtered and washed three times with ethanol / water to remove impurities.
[0050] (2) Add 0.88g of nano-zero-valent iron-carbon nanotube composite material and 0.099g of vitamin B to 660ml of N,N-dimethylformamide solution. 12 The solution was sonicated for 1 hour and stirred at room temperature for 20 hours. Subsequently, the solution was centrifuged, and the supernatant was discarded. The precipitate was washed with DMF and centrifuged twice until the supernatant was colorless. Finally, it was washed with deionized water and centrifuged twice, then freeze-dried to obtain vitamin B12. 12 Carbon nanotube composite material co-loaded with nano-zero valent iron.
[0051] Using dichloroethane as the target pollutant, the activity of the above solution was tested. 26 mL of deoxygenated deionized water and 0.104 g of vitamin B were added to a 52 mL reagent bottle. 12 Carbon nanotube composites were co-loaded with nano-zero-valent iron, sealed tightly with an aluminum cap fitted with a PTFE septum, and then dichloroethane stock solution was added to ensure an initial concentration of 10 ppm. The reagent bottle was then placed in a service incubator and maintained at a constant temperature of 25°C. The results are as follows: Figure 4 As shown, the degradation performance of this material is better under alkaline conditions than under acidic conditions.
[0052] Table 3 Vitamin B 12 The removal rate of dichloroethane by carbon nanotubes co-supported with nano-zero valent iron within 7 hours
[0053] 5 82.91% 6 81.32% 7 92.74% 9 97.5% 10 100% .
Claims
1. A type of vitamin B 12 A method for preparing a composite material of carbon nanotubes co-supported with nano-zero-valent iron, characterized in that... Includes the following steps: 1) Take the prescribed amount of ferrous sulfate heptahydrate and carbon nanotubes, add deionized water and mix. Stir and purge with N2 to remove dissolved oxygen to obtain a suspension. The mass ratio of ferrous sulfate heptahydrate to carbon nanotubes is 1.5-2.5:1, and the material-to-liquid ratio of carbon nanotubes to deionized water is 0.6-0.7g:155-165mL. 2) Add sodium borohydride solution dropwise to the suspension emulsion in step 1), and carry out the reduction reaction by vigorous stirring under N2 conditions. After the reduction is completed, filter the black suspension emulsion and wash it three times with ethanol / water to remove impurities, and obtain the nano-zero-valent iron-carbon nanotube composite material. 3) Add vitamin B to the N,N-dimethylformamide solution. 12 The nano-zero-valent iron-carbon nanotube composite material obtained in step 2) was ultrasonically treated, stirred at room temperature, centrifuged and the supernatant was discarded. The precipitate was washed with DMF and centrifuged twice until the supernatant was colorless. Finally, it was washed with deionized water and centrifuged twice, and then freeze-dried to obtain vitamin B1. 12 A composite material of carbon nanotubes co-supported with zero-valent iron nanoparticles, wherein the ratio of the zero-valent iron carbon nanotube composite material to N,N-dimethylformamide solution is 1g:700-800ml, and the vitamin B... 12 The mass ratio of carbon nanotubes to carbon nanotubes is 0.01-0.
25.
2. A vitamin B complex as described in claim 1 12 A method for preparing a composite material of carbon nanotubes co-supported with nano-zero-valent iron, characterized in that... In step 1), N2 is purified N2 with a purity greater than 99%.
3. A vitamin B complex as described in claim 1 12 A method for preparing a composite material of carbon nanotubes co-supported with nano-zero-valent iron, characterized in that... The vigorous stirring time in step 2) is 30 minutes.
4. A vitamin B complex as described in claim 1 12 A method for preparing a composite material of carbon nanotubes co-supported with nano-zero-valent iron, characterized in that... In step 3), the ultrasonic treatment time is 1 hour, and the stirring time at room temperature is 20 hours.
5. Vitamin B prepared by any one of claims 1-4 12 Application of carbon nanotube composite materials co-loaded with nano-zero valent iron in the treatment of wastewater, polluted soil and polluted groundwater.
6. The application as described in claim 5, characterized in that... The wastewater, contaminated soil, and contaminated groundwater contain at least one of the following: heavy metals, pesticides, azo dyes, halogenated organic compounds, and / or nitro-substituted organic compounds.